2016
DOI: 10.1089/apc.2016.0135
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Recruiting People Who Use Drugs for HIV-Related Biomedical Research: Perspectives from the Field

Abstract: Recruitment of people who use drugs (PWUD) for HIV-related research has been undertaken since early in the epidemic. In early studies, recruitment was often performed by outreach workers with familiarity with the target population, who distributed risk reduction materials, and administered the surveys being conducted on drug use and risk behaviors. The evolution of effective treatments for HIV has provided opportunities for PWUD to participate in biobehavioral studies testing the efficacy of medical treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 6 publications
4
18
0
Order By: Relevance
“…21 While the loss of participants from recruitment to screening was substantial, at approximately 50%, this is not surprising given the unstable life styles of many PWID. Importantly, close to 90% of those who were screened and found eligible for the study completed all components.…”
Section: Discussionmentioning
confidence: 99%
“…21 While the loss of participants from recruitment to screening was substantial, at approximately 50%, this is not surprising given the unstable life styles of many PWID. Importantly, close to 90% of those who were screened and found eligible for the study completed all components.…”
Section: Discussionmentioning
confidence: 99%
“…Since studies on research recruitment of women with SUD were limited, the search was broadened to include research recruitment of people who use drugs (PWUD). Ten studies were relevant; seven in international settings (Boucher et al, 2017;Brown et al, 2019;Grové, 2019;MacVicar, Humphrey, & Forbes-McKay, 2018;Sirdifield, Owens, & Brooker, 2016;Thong, Ulph, Barrowclough, & Gregg, 2019;Thornton, Harris, Baker, Johnson, & Kay-Lambkin, 2016) and three in the United States (Ballard, Cooper, & Young, 2019;Batista et al, 2016;Ryan, Smeltzer, & Sharts-Hopko, 2019). The literature emphasized individual factors as prominent challenges regarding research recruitment of women with SUD and PWUD.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One author used indirect recruitment of offenders on probation to minimize researcher bias but preferred direct recruitment to protect individual rights of research participation (Sirdifield et al, 2016). Other investigators recommended direct recruitment to promote researcher familiarity with the community (Batista et al, 2016;Boucher et al, 2017;MacVicar et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…We aimed for PWIDs who were attending at MOUD clinic due to their availability. Previous research in the United States (US) revealed several challenges in recruiting PWIDs from the community [27]. In this case, using participants at the MOUD clinic helped to overcome some of the challenges observed in the US and this facilitated getting the appropriate participants with low drug withdrawal effects that could hinder cooperation.…”
Section: Population and Participantsmentioning
confidence: 99%